PENERAPAN MODEL PEMBELAJARAN SITUATION-BASED LEARNING TERHADAP PEMAHAMAN MATEMATIS SISWA KELAS X SMA - Junedi, Beni; Susanti, Ade (Journal of Didactic Mathematics, 2020)
The research aims to find out the students' mathematical understanding using situation-based learning model students of class X IPA, the type of research used is quasi-experimental design research, taking class X IPA 3 as an experimental class and class X IPA 2 as a control class. The technique used in this sampling is cluster random sampling. Research instruments in the form of tests to determine the level of mathematical understanding of students. The data obtained will be analyzed with the hypothesis test t-test. Hypothesis test results obtained a significant value <0.05 which is 0.049 <0.05. Based on these results it was concluded to reject H0 and accept Ha. This means the average student's mathematical understanding ability using the Situation-Based Learning model is better than the average student's mathematical understanding ability using conventional learning.